The Pattern of Communication Legal Advisor with Defendant In Indonesian Courtroom - Widodo, Aan; Rahmat Hidayat, Dadang; Venus, Anter; Suseno, Sigid; ., . (International Journal of Engineering and Technology, 2018)
This article aims to illustrate the pattern of communication between legal Advisor and the defendant in court as one form of communication in the courtroom. This study addresses the research question: how is the communication pattern of legal advisor with the defendant in the courtroom at the Central Jakarta District Court. This research uses qualitative research approach, research method is ethnography of communication, with an interpretive paradigm. The results of this study indicate that communication between the legal advisor with the defendant in the courtroom begins at the time of the indictment hearing, the hearing, the prosecution and the verdict. The form of communication that emerged in the trial process through advocacy. Advocacy is a form of communication of legal Advisor with the defendant, with the primary objective of providing an understanding to the defendant about the legal information and the punishment that the defendant will receive.Â Â